PEMAHAMAN SISWA TENTANG HUKUM THAHARAH DALAM PERSPEKTIF FIQIH - Mohammad Qolbun Salim (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
This study aims to analyze students’ understanding of the laws of thaharah from a fiqh perspective and the factors influencing it. The main problem addressed in this research is the low level of students’ understanding, which is not only conceptual but also practical in daily life. This research employs a qualitative approach with a descriptive type. Data were collected through observation, in-depth interviews, and documentation involving students and fiqh teachers. The results show that students generally possess basic knowledge of thaharah, such as its definition and types; however, their understanding remains superficial and limited to memorization. Students face difficulties in comprehending more complex concepts, such as distinctions between types of impurity (hadas), categories of najis, and proper purification methods. In addition, students’ practical application of thaharah is not fully aligned with fiqh regulations. Factors affecting students’ understanding include less interactive teaching methods, lack of practical learning experiences, and family background. Therefore, more interactive, contextual, and practice-oriented learning strategies are needed to improve students’ understanding of thaharah effectively.